PROBLEMATIC ASPECTS OF FINANCIAL RISK ASSESSMENT METHODOLOGY IN STEVEDORING COMPANIES (World Science, 2019)
The study is dedicated to identification of problematic aspects of financial risk assessment methodology on the example of stevedoring companies. In research established the list of issues for improvement the methodology of financial risk assessment both in theoretical and practical aspects. Formulated industry features of the stevedoring companies’ activity, relevant factors from the perspective of financial risk impact on results of activity, among which are distinguished: loss of net sales, exchange rate instability and decrease of financial stability. It was found that the loss of net income from the sale of state stevedoring companies of Ukraine occurred: due to the failure to fulfill the plan of cargo processing by reducing the number of the number of ship-measures and change of the nomenclature of cargo towards the less profitable and instability of the US dollar. Particular attention is paid to assessing the level of financial stability of state-owned stevedoring companies in Ukraine and identifies a downward trend in recent years. It is argued that the definition of factors that affect financial risks should be conducted using factor analysis, mathematical models that require comprehensive consideration of uncertainty factors and related to the peculiarities of stevedoring companies operation. The feasibility of drawing up a financial risk map and the options of management's response to their presence have been proved.